2011
DOI: 10.4236/snl.2011.13015
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Preparation and Characterization of Zinc Phosphate Nanocrystals with Modified Surface

Abstract: The surface-modified zinc phosphate (Zn<sub>3</sub>(PO<sub>4</sub>)<sub>2</sub>) nanocrystals were synthesized by a facile and efficient one-step ultrasonic-template-microwave (UTM) assisted route. The crystal structure, optical properties and morphologies of zinc phosphate nanocrystals were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy and transmission electron microscope. And the TEM image showed that the product had good d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 15 publications
(15 reference statements)
0
38
0
Order By: Relevance
“…49, 50 The additional peak at 1650 cm −1 is due to the presence of either crystalline water or more likely, the amide I mode from bound serum proteins. 42, 43, 50, 56 These results indicate the species formed are a complex mixture of nZnO, retained proteins from fetal bovine serum (FBS) in the media and insoluble precipitate formation that is likely an amorphous mixture of zinc phosphate and carbonate species…”
Section: Resultsmentioning
confidence: 99%
“…49, 50 The additional peak at 1650 cm −1 is due to the presence of either crystalline water or more likely, the amide I mode from bound serum proteins. 42, 43, 50, 56 These results indicate the species formed are a complex mixture of nZnO, retained proteins from fetal bovine serum (FBS) in the media and insoluble precipitate formation that is likely an amorphous mixture of zinc phosphate and carbonate species…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, residue from PA66þS400-750 obtained from tubular furnace under controlled condition shows well defined diffraction pattern. Comparison with the literature and database search [14,[53][54][55][56][57][58] reveals that it is a mixture of several species like dehydrated form of α-hopeite (Zn 3 (PO 4 ) 2 , Zn(PO 3 ) 2 and Zn 2 (P 2 O 7 ). It has been observed that polymer medium often acts as a sacrificial matrix to generate crystalline, phase pure ZnPO.…”
Section: X-ray Powder Diffraction Studies (Xrd)mentioning
confidence: 98%
“…The theoretical values are estimated based on molecular formula given in Fig. 1 and the SZM product formed according to the chemical reaction (v) [29]. The result of the elemental analysis confirms the formation of SZM compound.…”
Section: Elemental Analysis Of Sodium Zinc Molybdate Nanoparticlesmentioning
confidence: 98%